Epidemiological investigation of an acute gastroenteritis outbreak in a tribal village near Madhya Pradesh-Maharashtra border - Bawa, Mukesh S.; Kinge, Amol D.; Borde, Ananta; Patil, Sarika; Gosavi, Shriram; Pagar, Vikrant; Rathod, Mamata; Chavan, Sushant; Shirpurkar, Mangesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Diarrhoeal diseases represent a major health problem in developing countries. Conservative estimates place the global death toll from diarrhoeal diseases at about two million deaths per year (1.7 - 2.5 million deaths), ranking third among all cases of infectious disease death worldwide. The prime purpose of an outbreak investigation is to control the outbreak, limit its spread to other areas and assess how preventive strategies could be further strengthened to reduce or eliminate the risk of such outbreak in future. Methods: It was a descriptive cross sectional study of epidemic occurred in Khetiya village, Dist Barwani (MP), population of 67,500 during 17 October 2016 to 17 November 2016. All the cases reported within last one week around the market place village in Khetiya, presenting with symptoms and signs of AGE (as per standard case definition of IDSP) and willing to participate in the investigation. Results: Males were 56.96%, & female cases were 43.03%. Majority of the study subjects lied between 20-40 years. The mean age was 30.15±5 years. Majority of the cases belonged to lower middle class SES (38%). 87% population was tribal, 48% cases were labourers, 42% were farmers and 10% were others. Conclusions: Males were 56.96%, & female cases were 43.03%. Majority of the study subjects lied between 20-40 years. The mean age was 30.15±5 years. Majority of the cases belonged to lower middle class SES (38%). 87% population was tribal, 48% cases were labourers, 42% were farmers and 10% were others.